Spatial repellents: The current roadmap to global recommendation of spatial repellents for public health use - Achee, Nicole L.; Perkins, T. Alex; Moore, Sean M.; Liu, Fang; Sagara, Issaka; Van Hulle, Suzanne; Ochomo, Eric O.; Gimnig, John E.; Tissera, Hasitha A.; Harvey, Steven A.; Monroe, April; Morrison, Amy C.; et al. (Current research in parasitology & vector-borne diseases, 2023)
Spatial repellent (SR) products are envisioned to complement existing vector control methods through the continual release of volatile active ingredients (AI) providing: (i) protection against day-time and early-evening biting; (ii) protection in enclosed/semi-enclosed and peri-domestic spaces; (iii) various formulations to fit context-specific applications; and (iv) increased coverage over traditional control methods. SR product AIs also have demonstrated effect against insecticide-resistant vectors linked to malaria and Aedes-borne virus (ABV) transmission. Over the past two decades, key stakeholders, including World Health Organization (WHO) representatives, have met to discuss the role of SRs in reducing arthropod-borne diseases based on existing evidence. A key focus has been to establish a critical development path for SRs, including scientific, regulatory and social parameters that would constitute an outline for a SR target product profile, i.e. optimum product characteristics. The principal gap is the lack of epidemiological data demonstrating SR public health impact across a range of different ecological and epidemiological settings, to inform a WHO policy recommendation. Here we describe in brief trials that are designed to fulfill evidence needs for WHO assessment and initial projections of SR cost-effectiveness against malaria and dengue. [Display omitted] •75 years ago the potential value of spatial repellents (SRs) for vector-borne disease control was recognized.•SR protective efficacy has been demonstrated for human Aedes-borne virus infections and efficacy results for human malaria infections are promising.•Initial projections indicate that SRs have public health and economic benefits.•Limited data exists on (i) human behavior and SR use and (ii) when and where SRs are needed.•WHO requirements on SR epidemiological efficacy are partially satisfied.